Key factors and underlying mechanisms for the enterprise systems lifecycle in public service organisations - SAXENA, DEEPAK KUMAR (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2017)
This is a longitudinal Critical Realist case study in the Enterprise Systems (ES) area within the Information Systems (IS) domain. Based on the literature review, it is identified that the majority of the ES research is conducted around the implementation phase. It usually reports a myriad of critical success factors (CSFs) that are generally conceived to be static throughout the ES lifecycle. The literature review also notes that the literature on ES-mediated organisation change usually subscribes to only technological/organisational imperative, employs variance based theorising, and is normally confined to a single level of analysis. Finally, it also notes that the ES literature normally does not pay attention to the implementation context and often it is implicitly assumed that findings from the private sector organisations would also apply to the public service organisations (PSO). Therefore, this study seeks to move beyond a list of CSFs and offers a mechanism-based critical realist account that captures the processual dynamics of the ES lifecycle in the PSO context. Therefore, the research question for this study is: what are the key factors and underlying mechanisms that underpin the enterprise system lifecycle in Irish public service organisations? The fieldwork was conducted in the Irish Blood Transfusion Services (IBTS) that engaged in three ES implementations over the period 2000-2015. The explanatory theoretical framework identifies four mechanisms underpinning the ES lifecycle in IBTS - affordance, control, institutionalisation, and market mechanism. These mechanisms manifest themselves via the emergence of various factors across the phases (Adoption, Acquisition, Implementation, Use and Maintenance, and Evolution) of ES lifecycle. The affordance mechanism at the work-system level is primarily associated with the features and constraints of the enterprise/legacy systems and business process requirements. The control mechanism operates at different levels during different phases of the ES lifecycle and public/health service context is found to be a major imperative for the prevalence of the control mechanism. The institutionalisation mechanism at the organisational level is associated with how different ES lifecycle activities are embedded in organisational activities. Finally, the market mechanism at the macrosocial level plays a crucial role due to the information asymmetry of the ES market and due to the existence of a dominant supplier in a niche (blood bank) market. These mechanisms and the interaction among them manifest in various CSFs during different phases of the ES lifecycle. A major finding of this study is that the relative importance of the CSFs varies not on during the phases of ES lifecycle but also across different instances of the ES lifecycle.
APPROVED
Keywords: Public Service; Enterprise System; ERP; Critical Realism; Factors; Mechanism; Case Study